Pengaruh Persepsi Mahasiswa Tentang Mata Kuliah Kewirausahaan dan Lingkungan Sosial terhadap Minat Berwirausaha Mahasiswa - Nur Faulina; Rizali Hadi; Melly Agustina Permatasari (Publikasi Berkala Pendidikan Ilmu Sosial, 2021)
This study ams to find out: (1) students 'perceptions about entrepreneurship courses, (2) social environment, (3) entrepreneurial interests, (4) influence of students' perceptions about entrepreneurship courses and social environment on entrepreneurship students interest in Economics Education FKIP Lambung University Mangkurat Banjarmasin. The research method uses quantitative descriptive, the research sample uses random sampling and the detarmination of the number of samples uslng the Slovln formuIa, while the number of study samples is 109 students consisting of 2016 and 2015 class of students. Data collection techniques using a questionnaire. The instrument trials use the validlty test and the reliabllity test. Data analysls techniques include analysis prerequisite tests which include normality and linearity tests. Hypothesis testing uses multiple regression tests with a significant level of 5%. Bassed on the resuIts of the study lt can be concledud as follows: I.) students' perceptions about entrepreneurship courses with a high category there are 61 (55.97%) students are 48 (44.03%) and in the low category there is none. 2.) social envronment with a high category does not exist, in the medium category there are 102 (93.58%) students and in the low category there are 7 (6.42%). 3.) interest in entrepreneurship with a high category there are 27 (24.78%) students are 82 (75.22%) and in the low category there are none. 4.) students' perceptions about entrepreneurship courses and the social envlronment have a posltive and signlficant effect simuItaneously or simultaneously on entrerpeneurial interest which is indicated by the caIculated F vaIue> F tabIe = 40.946> 3.080 and sig. 0.00 < 0.05, it can be concIuded that students' perceptions about entrepreneurship courses (X1) and social environment (X2) simultaneously influence the interest in entrepreneurship (Y). With R2 (R Square) of 0.660 or 66%, this means that the simultaneous influence of students 'perceptions about entrepreneurship courses and students' social environment is 66%, and the remaining 34% is influanced by other variables.